Uncoupling phototoxicity-elicited neural dysmorphology and death by insidious function and selective impairment of Ran-binding protein 2 (Ranbp2) - Cho, Kyoung-in (FEBS Lett, 2015)
Morphological disintegration of neurons is coupled invariably to neural death. In particular, disruption of outer segments of photoreceptor neurons triggers photoreceptor death regardless of the pathological stressors. We show that Ranbp2(−/−)::Tg-Ranbp2(CLDm) mice with mutations in SUMO-binding motif (SBM) of cyclophilin-like domain (CLD) of Ranbp2 expressed in a null Ranbp2 background lack untoward effects in photoreceptors in the absence of light-stress. However, compared to wild type photoreceptors, light-stress elicits profound disintegration of outer segments of Ranbp2(−/−)::Tg-Ranbp2(CLDm) with paradoxical age-dependent resistance of photoreceptors to death and genotype-independent caspase activation. Ranbp2(−/−)::Tg-Ranbp2(CLDm) exhibit photoreceptor death-independent changes in ubiquitin-proteasome system (UPS), but death-dependent increase of ubc9 levels. Hence, insidious functional impairment of SBM of Ranbp2’s CLD promotes neuroprotection and uncoupling of photoreceptor degeneration and death against phototoxicity.